Entrepreneurship mentoring program and training in Dusun II, Susukan, Banjarnegara - Tentama, Fatwa; Rahayu, Tika; Handayani, Nurrina; Yuliania, Devi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
This service aims to provide entrepreneurship training to the Dusun II people, Susukan, Banjarnegara. The method used in this service is lecture, discussion and practice, and roleplay. This program targets homemakers, adolescents, and kindergarten students in Dusun II, Susukan. Homemakers and adolescents are given a program consisting of lectures on entrepreneurial motivation and the practice of making creative products using secondhand goods. At the same time, kindergarten students are given a roleplay program for entrepreneurship by playing the role of seller and buyer. Through this program, the people of Dusun II Susukan, Banjarnegara, learned the importance of entrepreneurship and the skills to process used materials into items of economic value. Furthermore, people can make various innovations to create various other creative products. In addition to bringing economic benefits, this activity has also improved the quality of human resources in Dusun II Susukan, Banjarnegara, by increasing their skills.